A ANALISIS PERSEPSI MASYARAKAT TERHADAP PT. KALTIM JAYA BARA DI LONG – LANUK KECAMATAN SAMBALIUNG: ANALISIS PERSEPSI MASYARAKAT TERHADAP PT. KALTIM JAYA BARA DI LONG – LANUK KECAMATAN SAMBALIUNG - Lisa Puspitasari (ECO-BUILD, 2018)
The purpose of research conducted is to obtain a picture of the perceptions and expectations of society against PT. Kaltim Jaya Bara in Long-Lanuk Sambaliung District, from economic aspect, social aspect, and public welfare aspect. The analysis tools used are IKM (Satisfaction Index). Where IKM is calculated by using "weighted average value" of each element. There are sixteen assessment elements / indicators reviewed. Based on the research results can be seen that the public perception of PT. Kaltim Jaya Bara in terms of economic, social, and public health is "Good Enough". This is indicated by the large Public Satisfaction Index of 2.81 and the Satisfaction Index score after converted 70.25 (Good Indicator). This means the hypothesis is accepted.